Simulasi Pengaruh Jumlah Lubang pada Ring Fiksasi Eksternal untuk Tulang Tibia - Krisdiyanto, Krisdiyanto (Universitas Muhammadiyah Yogyakarta, 2018)
External fixation is a device that is placed out of soft tissue. External fixation device is used to heal open fracture. Open fracture is fracture that soft tissue is broken. That device consist of pin, rod, and clamp. We should pay attention of external fixation stiffness. Number of rod can be increased to get this device more stabil. That device should be stabil so fracture position and pin track doesnâ€™t move. External fixation that consist three rod usually Â Â use rin. This research aims to get the effect of external fixation ring holes number to stiffness.